Thyroid-associated Orbitopathy: Quantitative Evaluation of the Orbital Fat Volume and Edema Using IDEAL-FSE - Yoko Kaichi; Keizo Tanitame; Hiroaki Terada; Hideki Itakura; Haruya Ohno; Masayasu Yoneda; Yuji Takahashi; Yuji Akiyama; Kazuo Awai (European Journal of Radiology Open, 2019)
Background and Purpose: To compare orbital quantitative data obtained by fast spin-echo iterative decomposition of water and fat with echo asymmetry and least-squares estimation (FSE-IDEAL) in patients with thyroid-associated orbitopathy (TAO) and healthy controls and to investigate the characteristics of these data in TAO patients. Materials and Methods: Twenty-two TAO patients (4 males and 18 females; median age 51.0 years) and 22 healthy subjects (5 males and 17 females; median age 50.5 years) underwent orbital T2-weighted FSE-IDEAL. The water fraction in orbital fat was defined as the signal intensity (SI) water / (SI water + SI fat). The orbital fat volume was measured on fat images. The degree of proptosis was evaluated using in-phase imaging. Mann–Whitney U test was used to compare these quantitative data in the two groups. In TAO patients we ascertained the correlation among these values with the Spearman's rank correlation coefficient. Results: In TAO patients, the water fraction (right and left, p = 0.04), fat volume (right and left, p = 0.03) and degree of proptosis (right and left, p < 0.01) were higher than in the controls. In TAO patients, only the water fraction and the fat volume of left orbit showed negative correlation (p = 0.01). Conclusion: The water fraction of orbital fat, the orbital fat volume and the degree of proptosis obtained with FSE-IDEAL were higher in TAO patients than in the controls. The water fraction was a new parameter for differentiating between TAO patients and healthy subjects. Keywords: fast spin-echo iterative decomposition of water and fat with echo asymmetry and least-squares estimation (FSE-IDEAL), thyroid-associated orbitopathy (TAO), water fraction, orbital fat volume, proptosis, quantitative evaluation